Clonal chromosomal alterations in fibroadenomas of the breast - Cavalli, L. R.; Cornelio, D. A.; Wuicik, L.; Bras, ATS; Ribeiro, EMSF; Lima, R. S.; Urban, C. A.; Rogatto, Silvia Regina [UNESP]; Cavalli, I. J. (Elsevier B.V., 2001)
A cytogenetic study on short-term cell cultures from 10 fibroadenomas of the breast is reported, Clonal chromosomal alterations were observed in all cases analyzed, involving preferentially chromosomes X, 12, 14, 20, and 22. Normal karyotypes were found in 34.9% of the cells. The present findings are discussed together with the reports on fibroadenomas and other benign lesions of the breast described in the literature. Although no specific chromosome abnormality to date can be attributed to a particular type of benign breast pathology, some recurrent alterations are starting to emerge and may characterize these benign breast lesions, differentiating them from their malignant counterparts. (C) 2001 Elsevier B.V. All rights reserved.